Serum galectin-3 level in systemic sclerosis - Koca, Suleyman Serdar; Akbas, Fatma; Ozgen, Metin; Yolbas, Servet; Ilhan, Nevin; Gundogdu, Baris; Isik, Ahmet (Springer London Ltd, 2014)
Systemic sclerosis (SSc) is an autoimmune disease of unknown etiology characterized by progressive fibrosis. Activated fibroblasts are mainly responsible for fibrosis in SSc. Galectin-3, a beta-galactoside-binding lectin, plays many important regulatory roles in both physiological and pathological processes including proliferation, apoptosis, inflammation, and fibrosis. The purpose of this study was to assess the serum galectin-3 levels in patients with SSc. Thirty-seven SSc patients, 23 systemic lupus erythematosus (SLE) patients (serving as patient control group), and 28 healthy volunteers were enrolled in this study. Disease activity and severity scores were detected with Valentini disease activity index and Medsger disease severity scale in the SSc group and SLE disease activity index and Systemic Lupus International Collaborating Clinics/American College of Rheumatology damage index in the SLE group. The serum levels of galectin-3, vascular endothelial growth factor, transforming growth factor-beta, and interleukin-6 were determined. Compared to the control group, the galectin-3 levels were higher in the SSc and SLE groups. The galectin-3 levels were not correlated with the disease activity and severity indexes in both patient groups. But, the serum galectin-3 levels were higher in the active SSc and SLE subgroups than in the inactive SSc (4.6 +/- 5.8 vs. 1.3 +/- 1.1 ng/ml, p = 0.015) and SLE (17.4 +/- 11.3 vs. 6.5 +/- 8.9 ng/ml, p = 0.019) subgroups. These results suggest that galectin-3, which is associated with fibrosis and inflammation by previous studies, may be a prominent biomarker of disease activity in SSc.
Keywords: Disease activity; Galectin-3; Systemic sclerosis